Bridge Plate Failure with Extensor Tendon Injury: A Case Report and Literature Review - Rachel Lefebvre; Jessica Intravia; Lisa Cao; Alidad Ghiassi; Milan Stevanovic (Case Reports in Orthopedics)
Background. Dorsal spanning plate fixation is an increasingly popular method of fixation for certain distal radius fractures. Published outcomes are encouraging, but complications are still reported. Methods. We present a case report of a 26-year-old woman with spanning plate breakage and extensor pollicis longus (EPL) metallosis, fraying, and near-complete rupture. The patient’s unsuccessful follow-up led to this complication. Metallosis and damage to the extensor indices (EI) and distal extensor carpi radialis longus (ECRL) were intraoperative obstacles for tendon transfer to restore EPL function. Results. Tendon transfer in the setting of bridge plate failure has not yet been described in the literature. There are reports of spanning plate failure indicating that breakage often happens through the plate’s holes and after fracture healing. Conclusions. The compounded complication of plate failure with extensor tendon injury emphasizes the important relationship between the local anatomy, barriers to patient care, and potential problems after spanning plate fixation.